1999
DOI: 10.1086/306859
|View full text |Cite
|
Sign up to set email alerts
|

New Wolf‐Rayet Galaxies with Detection of WC Stars

Abstract: We report the discovery of two new Wolf-Rayet (WR) galaxies: Mrk 1039, and F08208+2816.Two broad WR bumps at 5808Å and 4650Å indicate the presence of WCE and WNL star population in all two sources. We also confirm the presence of WR features in Mrk 35, previously detected in a different position. The observed equivalent width of the WR bump at 4650Å and the derived number ratios of WR/(WR+O) imply that star formation in these sources takes place in short burst duration. Comparisons with the recent models of WR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
5
19
0
Order By: Relevance
“…This seems to indicate an inhomogeneous distribution of the dust within the galaxy, the southern regions being dustier than the remainder of the system. Huang et al (1999) also derived low extinction values in the center of IRAS 08208+2816, which they explained by considering the presence of a galactic wind in the galaxy, but we do not detect these structures in our deep Hα images (see Fig. 10 of Paper I).…”
Section: Physical Conditions Of the Ionized Gasmentioning
confidence: 51%
See 1 more Smart Citation
“…This seems to indicate an inhomogeneous distribution of the dust within the galaxy, the southern regions being dustier than the remainder of the system. Huang et al (1999) also derived low extinction values in the center of IRAS 08208+2816, which they explained by considering the presence of a galactic wind in the galaxy, but we do not detect these structures in our deep Hα images (see Fig. 10 of Paper I).…”
Section: Physical Conditions Of the Ionized Gasmentioning
confidence: 51%
“…The first spectroscopic data of IRAS 08208+2816 were obtained by Huang et al (1999), who reported the detection of both a nebular and broad He ii λ4686 emission line. They also detected the red WR bump, C iv λ5808, suggesting the presence of both WNL and WCE populations in the starburst.…”
Section: Iras 08208+2816mentioning
confidence: 99%
“…However, Steel et al (1996) note that the galaxy has relatively regular outer isophotes in optical light and that all of the star-forming regions have the same redshift. Steel et al also find approximately the same metallicity for both regions A and B of 12 þ log (O=H) ¼ 8:4 (roughly 1 3 the solar value); using a different slit location, Huang et al (1999) find a metallicity of 12 þ log (O=H) ¼ 8:3. This evidence leads Steel et al to conclude that the star formation in Haro 3 is most likely selfinduced.…”
Section: Introductionmentioning
confidence: 85%
“…We suspect that maybe knot #1, which hosts the youngest and most powerful burst in the system, is the only area where a substantial population may be present. Thus, aperture effects and the position of the slit can play an important role in the detection of WR features, as some authors have previously pointed out (Huang et al 1999;López-Sánchez et al 2004a,b).…”
Section: Wr Populationmentioning
confidence: 93%